1986
DOI: 10.1111/j.1752-1688.1986.tb01887.x
|View full text |Cite
|
Sign up to set email alerts
|

DOMESTIC WASTEWATER TREATMENT BY PEATLANDS IN A NORTHERN CLIMATE: A WATER QUALITY STUDY1

Abstract: The use of peatlands as the main form of wastewater treatment in a northern climate was studied for the James Bay Energy Society. The Fontanges campsite (70° 17′ 30″ W; 54° 34′ 00″ N) was chosen as the study site. In less than 1.5 km from the point of discharge BOD5, COD, total hardness, inorganic carbon, orthophosphates, total phosphorus, ammonia and total nitrogen were reduced by at least 90 percent. The peatland treatment system studied is divided into four components, each having a specific function. The f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

1988
1988
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 2 publications
0
4
0
Order By: Relevance
“…Wetlands have been used as a means of tertiary treatment of polluted effluents for several years (Dierberg and Brezonik, 1986b;Dubuc et al, 1986). Fritz and Helle (1986) have shown that this natural epuration is economically more profitable than the conventional chemical epuration, and Deghi et uf., (1980) have stressed that it does not adversely affect the stocking capacity of the wetland used.…”
Section: Resultsmentioning
confidence: 99%
“…Wetlands have been used as a means of tertiary treatment of polluted effluents for several years (Dierberg and Brezonik, 1986b;Dubuc et al, 1986). Fritz and Helle (1986) have shown that this natural epuration is economically more profitable than the conventional chemical epuration, and Deghi et uf., (1980) have stressed that it does not adversely affect the stocking capacity of the wetland used.…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, water quality improvement in sub-arctic and arctic wetlands receiving municipal and domestic wastewater has been demonstrated by authors such as Chouinard et al (2014), Yates et al (2012Yates et al ( , 2014,), Heinke (1993, 1995),), Dubuc et al (1986), andWright (1974). The authors identified the need for additional research on treatment mechanisms within the arctic wetlands, which requires characterization of the physical, hydrological, hydraulic, and biogeochemical context; treatment performance assessments; and long-term monitoring.…”
Section: Introductionmentioning
confidence: 95%
“…Wetlands often function as sinks for nutrients in high concentrations (reviews by Nixon andLee 1986, Johnston 1991 ). Success of natural and constructed wetlands for water quality improvement with high concentrations of nutrients (e.g., domestic wastewater) has been documented in a number of studies (e.g., Boyt et al 1977, Odum et al 1977, Tilton and Kadlec 1979, Dierberg and Brezonik 1983, Heliotis and DeWitt 1983, Nichols 1983, Dubuc et al 1986, Richardson and Marshall 1986, Knight et al 1987, Brodrick et al 1988, Brix and Schierup 1989, Knight 1990, Busnardo et al 1992, Cooke 1992, Gumbricht 1992, 1993, Brix 1994, Kadlec 1994, although some cases have documented phosphorus export after a number of years (Kadlec 1985, Knight et al 1987. Richardson (1985), Walbridge (1993), and Reddy and D'Angelo (1994), among others, have pointed out the importance of the chemical composition of parent soils in wetlands for the retention of phosphorus.…”
Section: Introductionmentioning
confidence: 99%